Optimasi Registrasi Kelas Persiapan Perkawinan Katolik Berbasis Mobile - Elisabeth Kurnia Andini; Agus Suhendar (STMIK Budi Darma, 2023)
Frequently, prospective couples encounter challenges when dealing with the registration process for Catholic marriage preparation classes. These difficulties stem from factors such as differences in domicile between the prospective spouses, time estimations, and significant costs associated with gathering the required documents and submitting data to the Church's secretariat. The primary objective is to establish a mobile-based optimization system for registering Catholic marriage preparation classes. This system is designed to simplify the registration process, allowing registrations from any location with a robust internet connection and the flexibility to adhere to the Church's specified deadlines. The proposed model focuses on enhancing the efficiency and effectiveness of the marriage preparation class registration system. It enables the display of class schedules and registration forms, facilitates document uploads, and manages registrant data using the Unified Modeling Language (UML). The resulting system offers a more practical and straightforward experience via the mobile platform by implementing the waterfall method and employing qualitative data processing techniques. Subsequently, the system undergoes black-box testing to ensure its functionality. The prototype for optimizing mobile-based Catholic marriage preparation class registration is developed using Android Studio tools and the Kotlin programming language. In this research, the application will be made to have a more practical and simple process using a mobile-based system that can display information on the schedule of marriage preparation classes and registration forms, provide a means for prospective brides to upload the required files, and store data information on marriage preparation class registrants.